(untitled) (Plant Tissue Culture and Biotechnology, 2017)
The availability of molecular marker systems allowed estimating the relationships among various taxa. This study was aimed at assessing the genetic diversity among ten aromatic rice (Oryza sativa L.) pools from Bangladesh by means of randomly amplified polymorphic DNA (RAPD) markers. These varieties were evaluated for polymorphisms after amplification with 10 decamer primers. A total of 60 RAPD fragments were generated among the assessed varieties with a polymorphism percentage of 80. Cluster analysis by the unweighted pair group method of arithmetic means (UPGMA) showed that these 10 varieties could be placed into two groups with a similarity ranging from 65 to 86% depicting adjacent association between Rajbhog and Kalijira‐12, whereas Maloti belongs to a separate group maintaining maximum distance from rest of the varieties. The analysis revealed that the intervarietal genetic relationship of several varieties is related to their center of origin. As expected, most of the varieties have a narrow genetic base. The present results could be used for the selection of possible parents to generate a mapping population and utilized by the breeders for assessing the genetic diversity of rice genotypes. Plant Tissue Cult. & Biotech. 27(2): 217-225, 2017 (December)